Green Governance and Collaborative Governance in Strengthening Sumatra's Forest Resilience - Marli I Alfikri; Rekho Adriadi; Novliza Eka Patrisia; Rosidin Rosidin (Publik : (Jurnal Ilmu Administrasi), 2026)
Forest degradation in Sumatra has become a critical environmental governance challenge driven by deforestation, tenure conflicts, weak law enforcement, and increasing hydrometeorological disasters. Conventional forest management, which relies heavily on top-down and enforcement-oriented approaches, has been unable to address the complex socio-ecological problems faced by local communities. This study aims to analyze how a collaborative governance model grounded in green governance principles strengthens forest resilience in the KHDTK Register 5 Bukit Daun, Bengkulu, while reducing tenure conflicts and supporting sustainable community livelihoods. A descriptive qualitative case study approach was employed. Data were collected through semi-structured interviews with 209 coffee farmers, field observations covering 1,992.69 hectares of the KHDTK area, and document analysis of government policies, village potential data, and institutional reports. Data were analyzed using an interactive qualitative analysis model involving data condensation, data display, and conclusion verification. The findings reveal that the transition from a coercive forest management model to a collaborative governance approach, facilitated by the university as a neutral bridging actor, successfully rebuilt trust among stakeholders, promoted social learning, and encouraged the adoption of adaptive agroforestry, riparian protection, and ecotourism-based livelihood diversification. These initiatives strengthened both ecological resilience and the adaptive capacity of local communities while reducing dependence on unsustainable land-use practices. The study also introduces the Tri-Helix Conservation Model, integrating universities, government agencies, and forest farmer groups as an institutional innovation for sustainable forest governance. This model offers a practical framework for strengthening forest resilience and can serve as a reference for collaborative forest governance in other protected forest areas facing similar socio-ecological challenges.